GRAIN-SIZE EVOLUTION IN SUBDUCTED OCEANIC LITHOSPHERE ASSOCIATED WITH THE OLIVINE-SPINEL TRANSFORMATION AND ITS EFFECTS ON RHEOLOGY - Riedel M.R.; Karato S.I. (My University, 1997)
We investigate the role of grain-size reduction during the olivine-spinel transformation on rheological properties of subducting slabs on the basis of a scaling model for microstructural development during nucleation and growth. In this model, the size of spinel grains nucleating at olivine grain boundaries is controlled by the relative rates of nucleation and growth, taking into account the impingement through the collision of grains due to growth. When the volume fraction of spinel reaches a certain threshold value (critical volume fraction ~ 1-10%, depending on the P-T conditions in the slab), the new phase will form a continuous film and will significantly reduce the strength of the two-phase aggregate, if spinel grain size is small. The size of spinel grains, δ0, at this stage is calculated and is shown to be highly sensitive to temperature. At relatively high temperatures (T > 1000 K), δ0 shows an Arrhenius-type dependence on temperature; that is, δ0 ~ exp(-E*/RT) with E* ~ 400 kJ/mol, whereas a more complicated temperature dependence is found at low temperatures (T < 900 K), where a grain-size reduction of up to 4 orders in magnitude is possible.Strength profiles of slabs due to combined effects of temperatures and of grain-size reduction are calculated. It is shown that: (1) the strength of slabs will have an unusual temperature dependence through the temperature dependence of grain size; and (2) a subducting slab has a complicated rheological structure containing a weak region below the tip of a metastable olivine-bearing wedge in a cold slab. Possible implications of these anomalous rheological structures of slabs on the dynamics of subduction are discussed, including the mechanisms of deep earthquakes.
Keywords: SUBDUCTION ZONES; RHEOLOGY; PHASE TRANSITIONS; DEEP-FOCUS EARTHQUAKES; GRAIN SIZE; KINETICS